Examining the Impact of Production Factors on Palm Oil Production Levels - Ismul Huda; Usma; Asman; Yuli Setiowati; Weni Widyawati; Ella Puspita (Universitas Muhammadiyah Malang, 2024)
This study aims to investigate the influence of various factors on oil palm production levels. Specifically, it seeks to analyze the effects of production range, fertilizer expenses, and labor on oil palm production. Furthermore, it intends to evaluate the impact of production variables, namely oil palm production zone, fertilizer costs, and labor, on oil palm production levels. Factors such as land area, fertilizer expenses, and workforce are critical variables affecting oil palm production, significantly influencing its productivity. Data was collected through observations, interviews, and surveys. The decision to conduct tests followed the purposive sampling approach, involving 26 respondents. The production components notably influence the production rate, particularly labor and fertilizer costs. However, the land area's production rate does not exhibit a significant effect. Approximately 92.5% of the production rate is attributable to the substantial contribution of production variables, with the remaining 7.5% influenced by other factors. Among these variables, fertilizer costs emerge as the most influential factor affecting oil palm productivity in Suliliran Baru.